CABERGOLINE THERAPY VERSUS REPEATED SURGERY IN POST-OPERATIVE RESIDUAL NON-FUNCTIONING PITUITARY ADENOMAS (NFPA): A 10-YEAR CLINICAL OUTCOME ANALYSIS - N, Normala; K, Nor Azmi; HAT, Amalina; SO, Syazarina; Y, Azyani; SZ, Syed Zulkifli (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Non-functioning pituitary macroadenomas (NFPAs) account for the highest proportion (1/3) of pituitary macroadenomas. Surgery is the primary mode of treatment of NFPAs however recurrence is seen in 50% of cases. There is no standard guideline in terms of treatment modalities for residual NFPAs with regards to repeat surgery, medical therapy, stereotactic or conventional radiotherapy. METHODOLOGY To analyse the clinical outcomes of secondary therapies for residual NFPAs following initial surgery by comparing cabergoline treatment versus repeated surgery and watchful surveillance. Data of patients with residual NFPAs following initial surgery from the endocrine and surgical clinics of Pusat Perubatan Universiti Kebangsaan Malaysia from 1997 to 2016 were retrieved and analysed. A total of 74 patients were enrolled, 30 patients in cabergoline group, 14 patients in repeated surgery group and 30 patients in watchful surveillance group. RESULTS The cabergoline group showed disease control in 86.7% of the patients and repeated surgery showed disease control in 42.9% of the patients (p value=0.002). The watchful surveillance group showed disease progression in 20% of patients compared with repeated surgery, 57.1% (p value=0.014). Complete suprasellar extension (p=0.035), complete parasellar extension (p=0.006) and tumor growth rate >10cm3 were predictive for negative outcomes of secondary therapies. CONCLUSION Residual tumour size ranging from 110 mm3 to 3, 200 mm3, 86% can be effectively controlled by cabergoline therapy. Patients who underwent repeated surgery tended to have bigger tumours and higher tumour growth rate; hence the outcome of surgery was not good as patients who received cabergoline. Decision to choose smaller size tumours for cabergoline therapy is seemingly justified.